Migration and women’s voice and agency in Senegal: Introducing a new survey - Beber, Bernd; Ebert, Cara; Kyle, Jordan; Riaz, Zara (International Food Policy Research Institute, 2024)
Millions of poor households around the world rely on migration to improve their economic circumstances and, increasingly, for resilience in the face of a changing climate. In vulnerable contexts, slow-onset climate impacts like water scarcity, rising temperatures, and more variable weather conditions are diminishing local economic opportunities and increasing food insecurity. Such climate impacts are projected to accelerate migration patterns, particularly out-migration from rural areas (Rigaud et al., 2018; SVR, 2023). While news reports on climate migration often emphasize communities leaving an area en masse due to a natural disaster, climate migration due to slow-onset climate shifts, which gradually lower crop yields and hinder agricultural livelihoods, more commonly implies a male household member migrating within a country, often seasonally, in order to send remittances back to his family.